1990
DOI: 10.1017/s1742758400019810
|View full text |Cite
|
Sign up to set email alerts
|

Beanfly infestation on common beans ( Phaseolus vulgaris L.) in Kenya

Abstract: The population patterns of eggs, larvae and puparia in the bean plants and leaf punctures made by adults were investigated during cropping (March-July and October-January) and noncropping (July-October) seasons at two sites in Kenya. The beans planted in noncropping seasons had more leaf punctures, eggs, larvae and puparia than beans planted in cropping seasons. Beans planted in noncropping season attracted unusually high population from surrounding weeds as well as previous crop which cause severe damage. Und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…Similarly, [36] showed that sowing date had an effect on population of ootheca, bean stem maggot and aphids and other arthropods attacking common beans. Studies by [37] also showed higher infestation by bean stem maggot in late or off-season planted crops.…”
Section: Agronomical Practicesmentioning
confidence: 90%
See 1 more Smart Citation
“…Similarly, [36] showed that sowing date had an effect on population of ootheca, bean stem maggot and aphids and other arthropods attacking common beans. Studies by [37] also showed higher infestation by bean stem maggot in late or off-season planted crops.…”
Section: Agronomical Practicesmentioning
confidence: 90%
“…In other agronomic studies, row spacing and plant density, weed control and stubble retention have been used to control bean stem maggot [37]. Other studies have demonstrated that sloping sites and border hedgerows that reduce wind speed promoted aphid landing and affected aphids and Ootheca distribution [38].…”
Section: Agronomical Practicesmentioning
confidence: 99%
“…The bean stem maggot attacks the bean plant as soon as the first pair of leaves begins to unfold (Odendo et al, 2005). It is most severe in late or off-season planted crops (Nderitu et al, 1990;Ochilo and Nyamasyo, 2011), hotter drier seasons, and in plants under stress such as poor soil fertility (Ampofo et al, 1994;Wang and Gai, 2001;Ojwang et al, 2010). Severe bean stem maggot attacks, especially during the early stages of plant growth, cause high yield losses.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the complexity in life cycle and high reproduction rate of this insect, it has become difficult to control using synthetic pesticides. [13] stated that row spacing and plant density have been used to control bean stem maggot. [14] indicated that high plant density decrease common bean virus incidence transmitted by aphids by 10% to 20%.…”
Section: Introductionmentioning
confidence: 99%